Course of Kinematic Parameters during the Course of Braking and Action of Dynamic Effects - Hudec, Pavol; Rojko, Eduard (Communications - Scientific letters of the University of Zilina, 2001)
The article deals with a course of kinematic values at rolling of car wheels during the course of braking focusing on experimental measurement of their time-base relations and effect of a braking slip of front wheels on a course of braking along with an effect of a gradient of braking deceleration build-up on a moment of wheel blocking from a view of safe car handling in direction.